2022
DOI: 10.3390/buildings12050542
|View full text |Cite
|
Sign up to set email alerts
|

Development of a BIM-Based Framework Using Reverberation Time (BFRT) as a Tool for Assessing and Improving Building Acoustic Environment

Abstract: Both the building design and the construction process determine the indoor acoustic quality of enclosures. A suitable indoor acoustic environment is crucial for the productivity and well-being of users. For this purpose, Reverberation Time (RT) is often calculated or measured in situ. Recently, Building Information Modelling (BIM) has provided a new paradigm to face building projects. Nevertheless, little research has been conducted on the optimisation of indoor acoustics using BIM methodology. In this context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Nevertheless, new methodologies are emerging in the architecture, engineering, construction and operation (AECO) sector as building information modelling (BIM). BIM is a methodology that offers new challenges and opportunities in the process of design, construction and maintenance of buildings [ 23 , 24 ]. BIM covers all phases of the building life cycle, and previous studies have shown its potential application during the building operation phase.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, new methodologies are emerging in the architecture, engineering, construction and operation (AECO) sector as building information modelling (BIM). BIM is a methodology that offers new challenges and opportunities in the process of design, construction and maintenance of buildings [ 23 , 24 ]. BIM covers all phases of the building life cycle, and previous studies have shown its potential application during the building operation phase.…”
Section: Introductionmentioning
confidence: 99%